A Short Proof of the Bolzano–Weierstrass Theorem. (1st September 2017) - Eidolon, Katrina; Oman, Greg
Summary: We present a short proof of the Bolzano–Weierstrass theorem on the real line which avoids monotonic subsequences, Cantor's intersection theorem, and the Heine–Borel theorem.